Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar - Salauddin Al Azad; Ehsan Kargaran; Maryam Saleknezhad; Yuanchao Cheng; Conghui Quan; Junyao Chen; Chihe Sun; Meysam Madadi; Fubao Sun (Chemical Engineering Journal, 2026)

Comparison study and mechanisms insight of AlCl3-catalyzed different organosolv pretreatment of lignocellulose: Enhancing enzymatic hydrolysis, lignin fractionation, and furfural production - Guojie Song; Salauddin Al Azad; Wenhao Hu; Meysam Madadi; Ashfaque Rahman; Chihe Sun; Fubao Sun (Bioresource Technology, 2026)

Machine learning-driven optimization of pretreatment and enzymatic hydrolysis of sugarcane bagasse: Analytical insights for industrial scale-up - Salauddin Al Azad; Meysam Madadi; Ashfaque Rahman; Chihe Sun; Fubao Sun (Fuel, 2025)

In-depth recognition of mixed surfactants maintaining the enzymatic activity of cellulases through stabilization of their spatial structures - Qiangqiang Liu; Meysam Madadi; Salauddin Al Azad; Chihe Sun; Ezhen Zhang; Junshu Yan; Abdolreza Samimi; Fubao Sun (Bioresource Technology, 2025)

WGS-based screening of the co-chaperone protein DjlA-induced curved DNA binding protein A (CbpA) from a new multidrug-resistant zoonotic mastitis-causing Klebsiella pneumoniae strain: a novel molecular target of selective flavonoids - Mohammad Habibur Rahman; Salauddin Al Azad; Mohammad Fahim Uddin; Maisha Farzana; Iffat Ara Sharmeen; Kaifi Sultana Kabbo; Anika Jabin; Ashfaque Rahman; Farhan Jamil; Sanjida Ahmed Srishti; Fahmida Haque Riya; Towhid Khan; et al. (Molecular Diversity, 2024)

Unraveling the mechanisms underlying lignin and xylan dissolution in recyclable biphasic catalytic systems - Xiuchao Xie; Meysam Madadi; Salauddin Al Azad; Yanming Qiao; Mahdy Elsayed; Mortaza Aghbashlo; Meisam Tabatabaei (Fuel, 2024)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Target-specificity of different amyrin subunits in impeding HCV influx mechanism inside the human cells considering the quantum tunnel profiles and molecular strings of the CD81 receptor: a combined in silico and in vivo study - Anika Jabin; Mohammad Fahim Uddin; Salauddin Al Azad; Ashfaque Rahman; Fawzia Tabassum; Pritthy Sarker; A K M Helal Morshed; Samiur Rahman; Fatima Fairuz Raisa; Musfiqur Rahman Sakib; Abeer Hasan Olive; Tabassum Islam; et al. (In Silico Pharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)